Development of Japanese Language Teaching Materials Based on Activity-Based Learning with A Communicative Language Teaching Approach for Vocational Training Participants - Rezki Fajriannoor; Robinson, Situmorang; Tuti, Iriani (CV. Media Digital Publikasi Indonesia, 2026)
This study examines how grammar-focused practices in vocational training institutes (LPKs) impair learners' communicative ability despite the Japanese Specified Skilled Worker (SSW) program. The study seeks to produce CLT-based activity-oriented Japanese teaching materials, assess their feasibility through expert validation, and test their effectiveness in improving speaking ability. This study's focus on LPK trainees as apprenticeship prospects and authentic, interactive assignments to improve communicative speaking abilities is innovative. This study was motivated by students' low communicative engagement in Japanese language practice and the need for materials that show communicative activities at vocational training institutes. Analyze, Design, Develop, Implement, and Evaluate comprise the ADDIE development model. The CLT technique was used to create and develop the instructional materials, emphasizing structural, quasi-communicative, functional communication, and social interaction learning activities. Learning media, Japanese language, and learning design professionals examined the instructional materials for viability. We then evaluated with interviews and questionnaires. The pretest-posttest findings of 17 LPK Kokorono Siji students were used to test effectiveness using N-Gain testing. The Japanese teaching materials were